Okay, this is a lot of information, but we'll take it one step at a time. Let's let "x" be Yoshi's age and "y" be Jana's age. We know the following:
X = 6y
X = 3 (√y - 7)
Since x both equals the first equation and the second equation, we can set the equations to themselves:
6y = 3 √(y - 7)
Begin simplifying by dividing three from both sides:
(6y)÷3 = √(y - 7)
Square both sides:
(2y)² = y - 7
If you look at this, it's beginning to look like a quadratic. In that case, move everything to one side, and set it to zero:
(2y)² - y + 7 = 0
Use the quadratic formula to solve. You should get two answers, and only one of them will be realistic. If you need a reminder, the quadratic formula is below, and 2 is "a", -1 is "b", and 7 is "c".
y = -b (+-) √(b² - 4ac)
------------------------
2a